The Social Network and #EndSARS Agitation: Protests against Police Brutality and Bad Governance in Nigeria - Theophilus Adedokun (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Protests in Nigeria have gained global attention in recent times and have attracted different explanations about their root causes. Violence may sometimes erupt because of protests; however, this does not usually happen until additional factors contribute to the protests. This study presents a Social Network Theory perspective on the agitation for #EndSARS among the Nigerian masses, especially the youths. #EndSARS is a movement against extra-judicial police brutality and a call to put an end to bad governance in Nigeria. This study was inspired by the following: (i) the rising popularity of social media in the present day; (ii) the worldwide increase in social media activism; and (iii) the diffusion of information by social media users. This study therefore employed the Social Network Theory in identifying the influence of social media on the diffusion of information about the #EndSARS movement and the sustenance of this movement over a long period, despite forces that have tried to silence the movement. This study argued that the sustenance of protests such as #EndSARS over a long period was dependent on factors such as: (i) that some individuals were more resistant to being influenced than others; (ii) that some individuals tended to be more responsive than others; and (iii) that some individuals seemed to be more affected than others (and were therefore more likely to pass information on to others). The findings revealed that protesters used emotional dynamics, collective identities, symbolic artefacts, and mutual values to sustain protests if their demands were not met on time.